Special Issue: The adaptive nature of linguistic behavior - Mirjam Fried (Linguistica Pragensia, 2022)
Not just diachronic change or synchronic variability in linguistic structure, but also the shape of speakers’ expressive strategies for navigating natural verbal interaction can be seen as reflections of the fundamental human capacity for adapting to novel communicative circumstances. The adjustments are observable at all layers of language — sounds, prosody, lexical changes, shifts in grammatical organization — and also pose questions concerning adaptation at both the individual and community levels. In this introductory framing of the present volume, the conceptual underpinnings of the quest for adequate explanations of adaptive processes are consistent with a set of assumptions that are associated with, broadly speaking, ‘socio-cognitive’ approaches to language: (i) socio-pragmatic and cultural grounding of verbal interaction, (ii) reference to domain-general cognitive capacities, and (iii) emergence of linguistic categories and their organization from recurring patterns of use. Linguistic analysis focused on the adaptive aspects of language and language use thus aims at capturing the speakers’ interactional competence; this includes both narrowly linguistic aspects and non-linguistic patterns of behavior, which, taken together, help us understand better all the factors involved in successful communication.